Attitudes of teachers and principals towards curriculum and school performance - Medina, Joel A. (2007)
This study sought to analyze the attitudes of teachers and principals towards curriculum development and instruction. It made use of mixed-method strategy expounded by Cresswell (2003) consisting of a descriptive-correlational research design and qualitative research design. The respondents were twenty-eight principals and 101 teachers-curriculum coordinators from the different elementary schools in Roxas City, Capiz. Questionnaires which include an attitude scale and Focus Group Discussion was also employed. Findings showed that teachers and principals have nonsignificant differences in their attitudes towards curriculum development and instruction. About 18.9 percent only in the variation of school performance was able to be explained by this variable.